PELATIHAN PENULISAN KARYA ILMIAH BAGI REMAJA UNTUK MENINGKATKAN IDE KREATIF, BERPIKIR KRITIS DAN INOVATIF PADA SISWA SMAN 1 KOTA PASURUAN - Ana Ahsana El-Sulukiyyah; Mardiningsih Mardiningsih (Universitas Mataram, 2023)
A good scientific work is one that is written with good preparation and systematics. Therefore it is necessary for students to get more information about writing scientific papers. This community service activity aims to provide provisions for new members of the Youth Scientific Work extracurricular (KIR) at SMAN 1 Pasuruan City. Students are expected to be able to write down their creative ideas to produce innovative scientific work based on the results of their critical thinking. The implementation of this activity goes through three stages, namely the presentation of material about scientific writing, the second is interactive discussion and the third is the drafting of scientific work. There were 60 students who took part in this training, they were new members of the Youth Scientific Work extracurricular (KIR). Based on the results of the activities described above, it can be concluded that the provision of youth scientific writing is very good where the level of student understanding is above 85%, namely: Understanding the definition of scientific work by 90%; Understanding Preparation for writing scientific papers by 94%; Systematic understanding of writing scientific papers by 88%; and Understanding of developing scientific writing ideas by 86%. The outputs of this activity are as follows: Training activities for writing scientific papers for youth have produced a work framework which will be continued and developed by each group; This activity adds to the understanding of activity participants who are new members of the Youth Scientific Work extracurricular (KIR); and activity participants have been able to plan research to be carried out through the stages of determining ideas, determining titles, targets or respondents, instruments used and preliminary background problems.